Emergence and Growth of Tall Fescue Seedlings after Postemergence Broadleaf Herbicide Application - Dani McFadden; Jack Fry; Steve Keeley (Kansas Agricultural Experiment Station Research Reports, 2021)
Effective weed control prior to seeding is essential for proper turfgrass establishment since competition from weeds can cause sward establishment to fail. Herbicides with multiple active ingredients from different chemical families could increase weed control efficacy, but hinder the establishment of newly seeded turf. Research trials were initiated in the fall of 2020 in Olathe and Manhattan, KS, to determine if tall fescue (Schedonorus arundinaceus) could be seeded earlier after application than stated on the herbicide labels. Overall, this study demonstrated that seeding between 0 to 14 days after an application of carfentrazone-ethyl + MCPP + 2,4-D + dicamba (SpeedZone), fluroxypyr + halauxifen-methyl + 2,4-D Choline (GameOn); or triclopyr + pyraflufen-ethyl + 2,4-D + dicamba (4-Speed XT) had little or no effect on tall fescue growth under the conditions evaluated in these experiments. In general, herbicide manufacturers must consider altering label reseeding intervals before using the results reported herein as guidelines.
Keywords: tall fescue; seeding; herbicide application